Rethinking Place through Literary Form
XXI, 284 p.
Keywords: Rethinking Place Through Literary Form regards the relationship between place and linguistic form as challenging real and perceived configurations of place and renegotiating geopolitically determined categories of the ‘centre’ and ‘periphery’. The volume argues that the rise of scattered communities, displaced physically and psychologically by urban and alienated geographies, necessitates linguistic negotiations of one’s locatedness in place as the chief means of uncovering and re-building identity. By looking at narrative re-imaginings of forgotten and interrupted intimacies between habitation and place from diverse parts of the world, the twelve chapters address the growing need to expand and alter approaches to literary representations of modernity and modes of self-location. Rupsa Banerjee is Assistant Professor of English at St. Xavier's University, Kolkata, India. Nathaniel Cadle is Associate Professor of English at Florida International University, USA. His first book, The Mediating Nation: Late American Realism, Globalization, and the Progressive State (2014), won the 2015 SAMLA Studies Book Award. .